The Rise of Sport Participation and Motivation of the Community in Sidoarjo - Luqmanul Hakim (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Studies reported that sports participation contributively has impacts on society, the economy, and health. However, research on sports participation in developing countries, including Indonesia, is limited. This study aimed to investigate the level of sports participation and motivation of the community. Furthermore, this research also examined the role of government and public sports organizations. The data analysis technique used was descriptive analysis, namely the data frequency from the questionnaire analysis. The study was conducted in Sidoarjo, Indonesia, involving 630 respondents and using a questionnaire developed from the Sports Development Index (SDI). The sampling technique used was purposive sampling. The samples should meet the criteria, including the specified age group, place of residence, not physically disabled, and could carry out daily activities independently. The study found that 41% of respondents regularly participated in sports activities, 20% of respondents irregularly participated in sports activities, and 39% of respondents were inactive. Soccer and running became the most played sports, performed by 26% and 18% of respondents. The main goal of exercising was to maintain health (64%). It was also found that most of them were engaged in the sports community. In addition, in the view of the community, the role of stakeholders in providing facilities, infrastructure, training, and sports socialization still needs improvements.